Proposal for the characterization of human development and its impact from professional training: the case of civil servants in the administrative career of the mayoralty of Tuluá (Valle del Cauca) 2014 (2019)
This article describes the results of the characterization on the impact and importancefor a person in an administrative career, the decision to continue or not with his or herdevelopment and professional training, which was carried out in the mayoralty of themunicipality of Tulua with the civil servants who were enrolled in the administrativecareer and are currently working there. In this process was carried out an extensive exploration of previous work and it wastaken into account the work done by Amartya Sen (2001), Martha Nussbaum (2012)and Manfred Max Neef (1998), who have performed some research related to humandevelopment and quality of life. They agree to specify that the human being is the centerof society and civilization, pointing with respect to human development a frameworkthat allows to live in dignity, as the needs, capabilities and the concept of a worthy life.Some research and articles were also presented in which are developed themes as theconflict work - family, quality of life, the situation of postgraduate studies in Colombia,among other topics The Primary data collection was carried out through the application of an online surveyto the civil servants enrolled in the administrative career in the mayoralty of Tuluáand from the information gathered it was performed an analysis of the data against theinitial approach and some conclusions were made from this